Pollutant removal in an experimental bioretention cell situated in a northern Chinese sponge city - Shi, Chunyan (Water science and technology : a journal of the International Association on Water Pollution Research, 2024)
© 2024 The Authors This is an Open Access article distributed under the terms of the Creative Commons Attribution Licence (CC BY 4.0), which permits copying, adaptation and redistribution, provided the original work is properly cited (http://creativecommons.org/licenses/by/4.0/).